Mechanical analysis of MEMS diaphragm for bladder pressure monitoring - Norliana, Yusof; Badariah, Bais; Burhanuddin Yeop, Majlis; Norhayati, Soin (2017)
Implantable bladder pressure sensor need to be very sensitive due to its very low pressure range detection. Hence, proper choice of a diaphragm structure is important as it would give an enormous impact on the sensitivity of a MEMS sensor. In this study, finite element (FEA) analysis is conducted to investigate the mechanical characteristics on four various diaphragm structures; clamped, slotted, corrugated and bossed square diaphragm of a capacitive MEMS pressure sensor. The MEMS diaphragm were designed and simulated using Comsol Multiphysics software. The static analysis was conducted in order to investigate the stress distribution, total displacement and capacitance meanwhile the modal analysis was conducted to determine the resonant frequency of each structure. From static analysis, it can be observed that slotted diaphragm has higher sensitivity compared to other structures. However, from modal analysis, it was found that the highest mechanical natural frequency is achieved by clamped diaphragm. From this study, it can be concluded that slotted diaphragm is the most suitable choice for designing the implantable MEMS bladder pressure sensor due to its high sensitivity and meet the requirement of desirable mechanical natural frequency of the sensor.